Technology Transfer from Public Research Institute to Community: A Case Study - Wati Hermawati (STI Policy and Management Journal, 2019)
Public funded research and development (R&D) institutes need to play a more active role in maximizing the utilization of their innovation/research results. One of the benefits of R&D innovation result is in the form of economic, social, environmental and cultural benefits for the improvement of human quality of life. Drawing from evidence of the case studies of R&D projects at Public Research Institute ‘A’ in Indonesia, we examined the technology transfer mechanisms into practical applications of the community. The mixed-method with good blend of qualitative and quantitative analysis is used in the case study. The case study demonstrates that there are five types of mechanisms for the technology transfer in this institution namely: direct transfer, through cooperation and interaction with multi stakeholders, patent and licensing, document transfer, and dissemination activities. The success of technology transfer to community were demonstrated by the increased ability of SMEs and farmers to replicate the technologies, increased their production, enlarge their market as well as increased new knowledge, skills, productivity, fertility of their rice fields, and decreased the use of chemical fertilizers by 40% and increased their household’s income by average about 30%.Keywords: technology transfer, public research institutes, communities, innovation